Two-stage aeration fermentation strategy to improve bioethanol production by scheffersomyces stipitis - Henriques, Tiago M. (2021)
Hardwood spent sulfite liquor (HSSL) is a by-product from pulp industry with a high concentration of pentose sugars, besides some hexoses suitable for bioethanol production by Scheffersomyces stipitis. The establishment of optimal aeration process conditions that results in specific microaerophilic conditions required by S. stipitis is the main challenge for ethanol production. The present study aimed to improve the ethanol production from HSSL by S. stipitis through a two-stage aeration fermentation. Experiments with controlled dissolved oxygen tension (DOT) in the first stage and oxygen restriction in the second stage were carried out. The best results were obtained with DOT control at 50% in the first stage, where the increase of oxygen availability provided faster growth and higher biomass yield, and no oxygen supply with an agitation rate of 250 rpm, in the second stage allowed a successful induction of ethanol production. Fermentation using 60% of HSSL (v/v) as substrate for S. stipitis provided a maximum specific growth rate of 0.07 h−1 , an ethanol productivity of 0.04 g L h−1 and an ethanol yield of 0.39 g g−1 , respectively. This work showed a successful two-stage aeration strategy as a promising aeration alternative for bioethanol production from HSSL by S. stipitis.